Childhood obesity and socio-economic class - Goyal, Rajni; Goyal, Puneet; Garg, Rajveer (International Journal of Research in Medical Sciences, 2017)
Background: Childhood obesity has reached epidemic levels in developed countries. Overweight and obesity in childhood are known to have significant impact on both physical and psychological health. The mechanism of obesity development is not fully understood and it is believed to be a disorder with multiple causes. There are supporting evidence that excessive sugar intake by soft drink, increased portion size and steady decline in physical activity have been playing major role in the rising rates of obesity all around the world. The aim of this study was to compare the obesity status of children (5-18 years) from the upper and middle socio-economic class. Methods: 400 children (200 boys and 200 girls) in the age group of 5-18 years from upper and middle socio-economic status (According to the modified version of Kuppuswamy’s socio-economic status scale) were selected as subjects for this study. Weight and height were measured in minimum acceptable standard clothing without shoes and socks and BMI was calculated. Because there are changes in body weight and height with age, BMI levels among children and teens need to be expressed relative to other children of the same age and sex. Number of children in each BMI-for-age-percentile-range were calculated. By using chi–square test an association of overweight/obesity with socio-economic class was studied in children. Results: The prevalence of overweight/obesity was more in upper socio-economic class boys in comparison with middle socio-economic class boys, more girls from upper socio-economic class were overweight/obese in comparison with middle socio-economic class girls and more girls were obese in comparison to boys from upper socio-economic class. Conclusions: The primary prevention could be the key plan for controlling the current epidemic of obesity and these strategies seem to be more effective in children than in adults.